BOOSTING YOUNG LEARNERS’ VOCABULARY THROUGH STORYBOARD AT TANAH OMBAK COMMUNITY - DIAN PURNAMA SARI (Bajang Institute, 2022)
In order to show the young learners how to talk in the most ideal ways, teachers ought to establish a powerful study hall climate where they have correspondence and all things considered, that can work on their expertise in communicating in English. This can happen when students team up in gathering to accomplish task by utilizing storyboard. Learning by using storyboard will make them ready to be dynamic since it is furnished with real exercises and significant errand. By taking a gander at grouping of pictures in organized, the students will be able to use appropriate diction trough a sequence of story lines elements.